Temporal coastal erosion changes analysis using remote sensing in northern Terkos lake - Kaya, İsmail. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2016., 2016)
Istanbul`s drinkable / useable water demand is provided by its nearby surface water resources (Yüzeysel Su Kaynakları Raporu, İMP 2005). The cities` exponentially increasing water need can not be satisfied with the existent water resources and new solutions should be provided to tackle the upcoming water shortness problem in the following decades. Terkos Lake is one of the most crucial surface water resources of Istanbul city. Inevitably, as a result of increasing population, irregular urbanization over the Istanbul in the last 20 decades, qualities of the water basins have been reduced dramatically. All precautions taken and aggressive rules and regulations imposed did not prevent the water basins enough from environmental pollution (Çodur, 2004). Remote sensing is a principle investigation method for large scale geographic locations. This method has been used for a lot research area (Gedik, 2006) like agricultural and geological branches. It is also a handy tool in environmental risk assessments. This study will initially focus on the satellite images which were converted into image vectors with the use of ArcMap and finally assess the status of Terkos Lake with the vector- time analysis.
Keywords: Coast changes -- Mathematical models.; Coast changes -- Terkos Lake (Istanbul, Turkey)